Implementasi Model Pembelajaran Lesson Study Praktikum Wisata Dalam Upaya Meningkatkan Pemahaman Konsep dan Berpikir Kreatif Mahasiswa Pada Mata Kuliah Media dan Sumber Belajar Di Prodi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam UMSU - Rizka Harfiani; Robie Fanreza (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
The purpose of this study was to study the level of understanding of the concept and creative learning of the Practicum Tourism Learning Learning model in the Media and Learning Resources courses at the PIAUD FAI UMSU Study Program. This research uses descriptive method, with research subjects 20 students from PIAUD FAI UMSU Study Program in Media and Learning Resources courses. This research was conducted in February 2018 until the end of June 2018. The form of this research is Classroom Action Research (CAR). The technique of collecting data using tests, observation, documentation and questionnaires. To answer the data validity, a triangulation technique was used, and to find out the results of this study descriptive analysis was used.From the results of the research obtained from the results of understanding and creative thinking PIAUD FAI UMSU, namely in the pre-action still 30% classical completeness, then increased in the first cycle reached 65% classical completeness, and increased again in the second cycle reached 92.5% classical completeness at a minimum score of 75, this result has exceeded the minimum classical completeness criteria of 85%.